Development of circadian rhythmicity and photoperiodic response in subdivisions of the rat suprachiasmatic nucleus - Bendová, Zdenka; Sumová, Alena; Illnerová, Helena (Brain research. Developmental brain research, 2004)
To ascertain whether the circadian rhythmicity of the ventrolateral (vl) suprachiasmatic nucleus (SCN) develops concurrently with that of the dorsomedial (dm) SCN and when the rhythmicity starts to respond to day length, i.e., to the photoperiod, rats with their offspring were maintained under either a long photoperiod with 16 h of light and 8 h of darkness per day (LD 16:8) or under a short, LD 8:16 photoperiod. The rhythms of spontaneous c-Fos immunoreactivity in the dm-SCN and of the light-induced c-Fos immunoreactivity in the vl-SCN were studied in the pups. In 3- and 10-day-old rats, the dm-SCN rhythm in spontaneous c-Fos immunoreactivty was already well expressed but a response to a photoperiod similar to that in adult rats has not yet been developed. The vl-SCN gate for insensitivity of c-Fos production to light at certain times was detected in 10-day but not yet in 3-day-old rats: in the latter, light exposure at any daytime induced high c-Fos immunoreactivity. In the 10-day-old pups, similarly as with adult rats, the gate was shorter under LD 8:16 than under LD 16:8, but the difference in the gate duration between the short and the long photoperiod did not yet attain that of adult animals. The data indicate that the circadian rhythmicity may develop sooner in the dm-SCN, than in the vl-SCN, whereas the photoperiodic response may develop sooner in the vl-SCN.
Keywords: Circadian Rhythm; protoonkogenní proteiny c-fos; Rats; Photoperiod; Animals, Newborn; Light; Analysis of Variance; těhotenství; fotoperioda; Time Factors; imunohistochemie; cirkadiánní rytmus; Darkness; Proto-Oncogene Proteins c-fos; světlo; mužské pohlaví; Rats, Wistar; novorozená zvířata; analýza rozptylu; nucleus suprachiasmaticus; počet buněk; krysa rodu Rattus; Suprachiasmatic Nucleus; Immunohistochemistry; ženské pohlaví; zvířata; Pregnancy; časové faktory; potkani Wistar; Cell Count; Female; Male; tma; Animals